The Application of The Guided Note-Taking (GNT) Learning Method and its Effect on Student's Understanding of Mathematics Concepts - Ayu Tunggal Rahayu; Arif Muchyidin; Budi Manfaat (Journal of General Education and Humanities, 2022)
This study aims to determine the effect of applying the Guided Note Taking (GNT) learning method on students' understanding of mathematical concepts. This study uses quantitative methods and is based on the previously discussed results. It can conclude that most students respond positively to the Guided Note Taking (GNT) learning method in learning mathematics because, based on the distribution of questionnaires, they obtained students' responses to the application of the Guided Note Taking (GNT) learning method, the percentage score obtained is 77% which is included in the strong category. In addition, students' understanding of mathematical concepts is included in the good category. The average value of students' mathematical concept understanding test results in the experimental class was 80.44, while the average value of the mathematical concept understanding test results in the control class was 75.67. This shows that the students' ability to understand mathematical concepts in the experimental class is better.